BUSINESS STRATEGY FORMULATION AND ITS IMPACT ON DIGITAL MARKETING (CASE STUDY ON WARUNG PETANI’S AND CATERING) - Ni Made Rai Christina Kusuma Dewi (Proceeding International Conference on Information Technology, Multimedia, Architecture, Design, and E-Business, 2024)
Warung Petani's and Catering is a restaurant located in the Karangasem area which was built with the concept of simplicity, namely a restaurant that prioritizes simple dishes with high quality. This restaurant has experienced a decline in the number of visits in recent years but always trying to survive amidst quite tight competition. This business needs to analyze the threats, opportunities, strengths and weaknesses that exist to deal with the problem of decreasing number of visits. This study aims to design a business strategy by analyzing the internal and external environmental conditions of the Warung Petani's and Catering business. Located on Jl. Veteran, Padang Kerta Village, Karangasem District, Karangasem Regency. The analysis technique used is the IFAS-EFAS Matrix. The results of the study indicate that the company's current business strategy is in quadrant V. This means that the company's correct business strategy to implement is the hold and maintain strategy by means of market penetration and product development.